The physiology of follicle selection - Zeleznik Anthony J (BMC, 2004)
Abstract During the follicular phase of the primate menstrual cycle, a single follicle usually matures to the preovulatory stage and releases its oocyte for fertilization and the potential establishment of pregnancy. In assisted reproductive technology procedures, it is desirable to override the natural process of follicle selection to produce many oocytes that are capable of being fertilized and undergoing normal embryo development. The goal of this chapter is to summarize the current views regarding the natural process of follicle selection in primates and to discuss how this process may be amplified to produce a greater number of oocytes.